Non-genomic Effects of Estrogen on Cell Homeostasis and Remodeling With Special Focus on Cardiac Ischemia/Reperfusion Injury - Puglisi, Rossella; Mattia, Gianfranco; Carè, Alessandra; Marano, Giuseppe; Malorni, Walter; Matarrese, Paola (Frontiers in Endocrinology, 2019)
This review takes into consideration the main mechanisms involved in cellular remodeling following an ischemic injury, with special focus on the possible role played by non-genomic estrogen effects. Sex differences have also been considered. In fact, cardiac ischemic events induce damage to different cellular components of the heart, such as cardiomyocytes, vascular cells, endothelial cells, and cardiac fibroblasts. The ability of the cardiovascular system to counteract an ischemic insult is orchestrated by these cell types and is carried out thanks to a number of complex molecular pathways, including genomic (slow) or non-genomic (fast) effects of estrogen. These pathways are probably responsible for differences observed between the two sexes. Literature suggests that male and female hearts, and, more in general, cardiovascular system cells, show significant differences in many parameters under both physiological and pathological conditions. In particular, many experimental studies dealing with sex differences in the cardiovascular system suggest a higher ability of females to respond to environmental insults in comparison with males. For instance, as cells from females are more effective in counteracting the ischemia/reperfusion injury if compared with males, a role for estrogen in this sex disparity has been hypothesized. However, the possible involvement of estrogen-dependent non-genomic effects on the cardiovascular system is still under debate. Further experimental studies, including sex-specific studies, are needed in order to shed further light on this matter.